Samut nord : l'exploitation de I'or du désert oriental à l'époque ptolémaique : avec deux chapitres sur les occupations pharaonique et médiévale du district minier - Redon, Bérangère (Fouilles de l'Institut français d'archéologie orientale du Caire, 2020)
"Located in the Eastern desert of Egypt, Samut North is a site entirely devoted to gold mining. Consisting of areas for the extraction and transformation of gold quartz and two vast buildings dedicated to housing, it was briefly occupied around 310 BC. Before they were destroyed in 2017, the remains of Samut North were exceptionally well preserved and their exploration represented a unique opportunity to fully study a mining facility at the height of gold mining in Egypt. It was also a chance to compare the evidence of the archaeological remains with the descriptions of the ancient mines left by Agatharchides of Cnidus, who lived in the 2nd century BC. The comparison of the data makes it possible to draw up an unprecedented panorama of the operating chain that produced part of the gold that Ptolemy, son of Lagos, needed to conduct his policy in the Mediterranean. The careful study of all the remains, including the most modest ones, also makes it possible to reconstruct the living conditions of the inhabitants (soldiers, logisticians, miners, including perhaps women) who, for some seasons, lived in the middle of the desert to exploit its riches. ... Added to these chapters is a study of three mining villages in Samut district dating back to the New Kingdom and the Middle Ages."--Back cover.